TA’LIK TALAK DAN KORELASINYA DENGAN KONSEP MASHLAHAT PERSPEKTIF ABU ISHAK ASY-SYATIBI - Sokhibul Imam; Abdur Rokhim; Jannati; Heri Ikhlas Khusaeri (Institut Agama Islam Darul Falah Bondowoso, 2025)
Marriage in Islam is part of the Prophet’s sunnah, not only as a form of worship but also as a legal institution, one aspect of which is the practice of ta’lik talak (conditional divorce) declared after the marriage contract. In Indonesia, this practice serves as a legal mechanism to protect wives from potential abuse of power by husbands. This study employs a qualitative method with a library research approach, drawing data from Abu Ishaq Al-Syatibi’s Al-Muwāfaqāt fī Uṣūl al-Sharī‘ah and relevant supporting literature. The results indicate that ta’lik talak is normatively justified under Article 45 paragraph 1 of the Compilation of Islamic Law (KHI) and aligns with the principle of maslahah (public interest) in Islamic legal theory. Ta’lik talak serves a dual function: as a moral reminder for the husband and as legal protection for the wife, preventing arbitrary actions and encouraging household harmony. According to Al-Syatibi, maslahah must protect essential human rights, serve collective good, and avoid subjective interests. Therefore, the practice of ta’lik talak embodies maqāṣid al-sharī‘ah (higher objectives of Islamic law), contributing to the realization of a harmonious and righteous family life. Keywords: Ta’lik Talak, Maslahah, Abu Ishaq Al-Syatibi, Compilation of Islamic Law